2012
DOI: 10.1128/jvi.07076-11
|View full text |Cite
|
Sign up to set email alerts
|

Serotype-Specific Neutralizing Antibody Epitopes of Human Adenovirus Type 3 (HAdV-3) and HAdV-7 Reside in Multiple Hexon Hypervariable Regions

Abstract: bHuman adenovirus types 3 and 7 (HAdV-3 and HAdV-7) occur epidemically and contribute greatly to respiratory diseases, but there is no currently available licensed recombinant HAdV-3/HAdV-7 bivalent vaccine. Identification of serotype-specific neutralizing antibody (NAb) epitopes for HAdV-3 and HAdV-7 will be beneficial for development of recombinant HAdV-3/HAdV-7 bivalent vaccines. In this study, four NAb epitopes within hexon hypervariable regions (HVRs) were predicted for HAdV-3 and HAdV-7, respectively, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…The hot spots for recombination are the major capsid genes, namely the hexon, penton base, and fiber genes (17,34). Therefore, the diversity of the major capsid genes, particularly in hexon loops 1 and 2, the penton RGD loop, and the fiber knob, which are associated with binding to neutralizing antibodies and receptors of the host, via recombination may result in escape from the host immune response and the acquisition of different organotropisms in HAdVs (18)(19)(20)(21)(22)(23)(24)(25)(26). Interestingly, our phylogenetic analysis demonstrated that many HAdV types, including our clinical isolates, share the sequences of different types in loop 1 of the hexon, the RGD loop of the penton base, and the fiber knob, thus suggesting evidence of drastic genetic evolution in these regions due to recombination events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hot spots for recombination are the major capsid genes, namely the hexon, penton base, and fiber genes (17,34). Therefore, the diversity of the major capsid genes, particularly in hexon loops 1 and 2, the penton RGD loop, and the fiber knob, which are associated with binding to neutralizing antibodies and receptors of the host, via recombination may result in escape from the host immune response and the acquisition of different organotropisms in HAdVs (18)(19)(20)(21)(22)(23)(24)(25)(26). Interestingly, our phylogenetic analysis demonstrated that many HAdV types, including our clinical isolates, share the sequences of different types in loop 1 of the hexon, the RGD loop of the penton base, and the fiber knob, thus suggesting evidence of drastic genetic evolution in these regions due to recombination events.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous reports demonstrated that HAdV-53 and HAdV-64 exhibited close relationships with different proteotypes in these regions (13,16). Since HAdVs contain neutralizing, hemagglutination, and receptor-binding epitopes in loops 1 and 2 of the hexon protein, the RGD loop of the penton protein, and the knob domain of the fiber protein, genomic analyses of these regions provide information on the immunogenicity and tissue tropisms of the HAdVs (18)(19)(20)(21)(22)(23)(24)(25)(26). Furthermore, the variation of these regions through recombination could result in escape from the host immunity and the acquisition of different organotropisms.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier published studies showed that Ad5 vectors with modifications to only HVR1 (63) or HVR5 (64) avoided Ad5 NAb in vitro and could induce transgene-specific immune responses in animals previously exposed to Ad5. However, more recent work indicates that Ad5-, Ad3-, and Ad7-specific NAb target multiple HVRs (65,66). Ad5-based hexon-modified vectors carrying HVRs 1 to 3, HVR 4, or HVR 5 of Ad48 underperformed relative to an Ad5 vector containing all HVRs of Ad48, indicating that modification to multiple HVRs is necessary for full immune avoidance in vivo (65).…”
Section: Discussionmentioning
confidence: 99%
“…The following strains of adenoviruses used in this study were obtained as previously described (Tian et al, 2011;Qiu et al, 2012;Zhang et al, 2009): recombinant adenovirus rAd3EGFP encoding a HAdV-3 GZ-01 genome and an enhanced green fluorescent protein (eGFP) with an E3 region deletion, hexon chimeric adenovirus rAd3egf/H7 generated by replacing the HAdV-3 hexon gene of the rAd3EGFP with the hexon gene from HAdV-7 GZ08 strain, epitope mutants (rAd3H7R1, rAd3H7R2, rAd3H7R5, and rAd3H7R7) from rAd3egf/H7 replaced with corresponding HAdV-3 epitopes, and epitope chimeric mutant rAdMHE3 from rAd3EGFP replaced with HVR5 of HAdV-7. All the adenoviruses were cultured in HEp-2 cells or AD293 cells as previously described (Tian et al, 2011).…”
Section: Virus Strains and Cellsmentioning
confidence: 99%
“…additional highly variable regions (Rux et al, 2003;Bradley et al, 2012;Yuan et al, 2009). Our previous study demonstrated that HVR1, 2, 5, and 7 of HAdV-3 contained neutralizing epitopes (Qiu et al, 2012).…”
Section: Introductionmentioning
confidence: 98%